Influence of emotional intelligence and teacher support on students' learning motivation at Public Junior High School in South Tangerang - Waliyati Waliyati; Erwin Erlangga; Rini Sugiarti (Institute of Computer Science (IOCS), 2026)
The purpose of this study is to look into how emotional intelligence and teacher support affect South Tangerang public junior high school students' learning. The research design is explanatory, and the methodology is quantitative. 130 students made up the research sample, which was selected with a 5% margin of error using proportionate stratified random sampling with the Slovin method. The data was examined using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach, and SmartPLS 4.1.0.8 software. Emotional intelligence significantly increased learning motivation (P-value < 0.05, path coefficient = 0.669). The research model successfully explained 94.8% of the variation in learning motivation (R² = 0.948). A comparison of the two independent variables reveals that emotional intelligence has a bigger influence than teacher support, demonstrating that internal elements are more important in shaping long-term learning motivation. This study emphasizes how crucial it is to raise students' emotional intelligence and teachers' socio-affective roles in fostering a supportive learning environment.